Lead(IV) reagents for the oxidation of alcohols to aldehydes - Buston, J; Howell, H; Moloney, M; Manson, VC; Thompson, R (1998)
Lead tetra(2-thiophenecarboxylate) oxidises benzylic and allylic alcohols to the corresponding aldehydes.